Benign prostatic hyperplasia and male lower urinary symptoms: A guide for family physicians - Farhad Fakhrudin Vasanwala; Michael Yuet Chen Wong; Henry Sun Sien Ho; Keong Tatt Foo (Asian Journal of Urology)
Male patients with lower urinary tract symptoms (LUTS) and benign prostatic hyperplasia (BPH) are increasingly seen by family physicians worldwide due to ageing demographics. A systematic way to stratify patients who can be managed in the community and those who need to be referred to the urologist is thus very useful. Good history taking, physical examination, targeted blood or urine tests, and knowing the red flags for referral are the mainstay of stratifying these patients. Case selection is always key in clinical practice and in the setting of the family physician. The best patient to manage is one above 40 years of age, symptomatic with nocturia, slower stream and sensation of incomplete voiding, has a normal prostate-specific antigen level, no palpable bladder, and no haematuria or pyuria on the labstix. The roles of α blockers, 5-α reductase inhibitors, and antibiotics in a primary care setting to manage this condition are also discussed. Keywords: Benign prostatic hyperplasia, Male lower urinary tract symptoms, Guideline, Family physicians